Concept of human error in an integrated household waste management system - Čeganjac, Zoran Kosta; Mihailović, Đorđe; Kostadinović, Jelena M. (Vojnotehnički glasnik / Military Technical Courier, 2013)
There are significant risks of mistakes made by those employed at various levels in organizations dealing with very responsible tasks in household waste management. Possibilities of protection against solid waste increase in accordance with the development of ecological responsibility.  Industralisation has resulted in waste proliferation which is becoming the major world problem, and will be a top priority for resolving in the future. New tehnologies for garbage management are emerging, and garbage producers discover new possibilities for the application of recycled materials. The clean air issue, although not being  a new one, is certainly one of the fastest growing issues concerning human influence on the environment. The concentration of greenhouse gases in the atmosphere is growing constantly. The subject of this work is to assess the risks referring to the formation of greenhouse gases as well as a possibility of human error occurence in the integral management of household waste.There is little data on the household waste composition and quantities of particular materials as far as our country is concerned. There is particularly little, or even no data on rural waste, because waste is usually neither collected nor disposed of in rural areas. An integral system of solid waste management is based on the analysis, discussion and definition of the methods and procedures for solid waste treatment, starting from the possibility of its reduction by chosing optimal ways for solid waste treatment from the place of its formation to its final disposal, harmless for the environment. The “Duboko” project of solid waste management is one of the latest projects in Serbia. In 2011, in the vicinity of Uzice, the Duboko landfill was opened as a common project of two cities and seven municipalities of the Moravicki District and the Zlatibor District. The mankind enters a new century with major ecological issues, such as an increased formation of waste materials of different origin and content in all three physical states, so that there is a huge responsibility of the employed in this area. The waste formed as a result of human activities is the following: cardboard, paper, plastic, textile, leather, furniture, glass, cans, household appliances, vehicles and their parts, sanitation devices, car tyres, construction material, sludge from waste water treatment plants, bio-hazardous waste (from hospitals, of animal origin, animal corpses and alike), etc.The recycling of waste material is an organizational-technical process the positive sides of which may be observed through the following: cost savings for primary raw materials, energy conservation, ecological efficiency and economical efficiency. Recycling is a dynamic process where materials intended for disposal are separated from the general waste flow.A possibility to predict, notice and prevent human error, regardless of the circumstances causing it, has a crucial importance for a continued process of waste collection from the very begining to its recycling and afterwards. The latest research carried out over the last decade of the past century keeps on the same track of treating the issue of human error causalty within an organization. Therefore, Van der Schaf (1992), based on his own results, concludes that »each time a manager, foreman, procedure or a part of the equipment behaves in an unexpected way thereby either preventing productive system from a likely collapse or re-establishing the safety&reliability levels required, these positive deviations may be revealed, reported and analysed in order to improve a quality-wise insight in the way the system is functioning as a whole«.